An Analysis of Maura’s Mom’s Daily Language: Code Mixing - Inne Maura Ahmad (Journal of English Education Studies, 2026)
This study aims to analyze the daily language use of an adult woman as influenced by her social environment. The research focuses on how environmental factors shape language habits, particularly the use of code-mixing in everyday communication. This study employed a descriptive qualitative method with a sociolinguistic case study approach. The subject of the study was an adult woman named Wiwin Herlina, who was selected purposively because she actively uses mixed languages in her daily interactions. The data were collected through direct observation and voice recording in natural communication situations. The collected data were then transcribed, classified, and analyzed using data reduction, data display, and conclusion drawing. The findings show that the subject was able to communicate in her daily life by mixing two languages. This language practice was influenced by her surrounding environment, which gradually formed a new habit in her communication style. The study concludes that the environment plays an important role in shaping an individual’s daily language use, especially in the practice of code-mixing. Therefore, code-mixing can be understood as a form of linguistic adaptation and cultural acculturation when used appropriately in daily communication.